Pemberdayaan Literasi Digital Melalui Optimalisasi Media Sosial pada Ikatan Pelajar Muhammadiyah Kota Sorong - Ermin; Faida Musa’ad; Nur Miswar; Muhammad Jundullah; Muhammad Surahmanto (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2026)
Digital literacy is an important competency for students in facing technological developments and the massive use of social media. However, the low ability of students to filter information, understand social media ethics, and maintain digital security remains a challenge, especially in the city of Sorong. This activity aims to empower students' digital literacy through the optimization of social media in the Muhammadiyah Student Association (IPM) of Sorong City. The implementation methods include digital literacy education, social media management training, and assistance in creating educational and ethical content. The activity evaluation was conducted using pretests and posttests to measure the increase in participants' digital literacy. The results showed an increase in the average digital literacy score of students from 55% in the pretest to 82% in the posttest, or an increase of 27%. These findings indicate that the optimization of IPM social media is effective as a means of digital literacy education and the formation of critical, safe, and productive social media behavior. This activity is expected to become a model for strengthening students' digital literacy that is sustainable and can be replicated in other student organizations.